2014
DOI: 10.1371/journal.pone.0105776
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Functional Metagenomic Annotation and the Mappability of Short Reads

Abstract: To assess the functional capacities of microbial communities, including those inhabiting the human body, shotgun metagenomic reads are often aligned to a database of known genes. Such homology-based annotation practices critically rely on the assumption that short reads can map to orthologous genes of similar function. This assumption, however, and the various factors that impact short read annotation, have not been systematically evaluated. To address this challenge, we generated an extremely large database o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 55 publications
1
63
0
Order By: Relevance
“…Commonly used sequencers have different error rates and patterns (Quail et al, 2012), but their effects on taxonomic (Sinha et al, 2015) and functional (Nayfach et al, 2015a) composition are surprisingly minimal (O’Sullivan et al, 2014). Read length, on the other hand, is a source of bias on its own (Carr and Borenstein, 2014; Nayfach and Pollard, 2015), in large part because it is more difficult to detect homology for short reads, especially when sampled from a taxonomic group that is poorly represented in reference databases (Wommack et al, 2008). Long-read technologies help with homology detection but are currently much lower throughput and also prone to insertion and deletion (indel) errors (Carneiro et al, 2012) that can affect read-mapping accuracy (Nguyen et al, 2014).…”
Section: Experimental Protocols Affect Results and Should Be Tracked mentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used sequencers have different error rates and patterns (Quail et al, 2012), but their effects on taxonomic (Sinha et al, 2015) and functional (Nayfach et al, 2015a) composition are surprisingly minimal (O’Sullivan et al, 2014). Read length, on the other hand, is a source of bias on its own (Carr and Borenstein, 2014; Nayfach and Pollard, 2015), in large part because it is more difficult to detect homology for short reads, especially when sampled from a taxonomic group that is poorly represented in reference databases (Wommack et al, 2008). Long-read technologies help with homology detection but are currently much lower throughput and also prone to insertion and deletion (indel) errors (Carneiro et al, 2012) that can affect read-mapping accuracy (Nguyen et al, 2014).…”
Section: Experimental Protocols Affect Results and Should Be Tracked mentioning
confidence: 99%
“…Studies examine different levels of taxonomic resolution, including individual strains (Box 2). As methods are rigorously benchmarked (Carr and Borenstein, 2014; Lindgreen et al, 2016; Nayfach et al, 2015a), iterative improvements and new approaches should soon enable accurate quantification of the abundances of individual taxa, genes, or pathways in a single metagenome.…”
mentioning
confidence: 99%
“…Here, we build upon previous work [7,[19][20][21][22] and use mock communities and simulated metagenomes to systematically evaluate and optimize metagenome annotation (Fig 1). To our knowledge, our approach represents the first end-to-end evaluation and optimization of metagenome annotation.…”
Section: Statistical Simulations Identify Best Practices In Metagenommentioning
confidence: 99%
“…Sample processing and library preparation can, for example, bias the predicted functional profile of a metagenomic sample 127 . A recent study systematically evaluated such homology-based annotation practices and demonstrated that variation introduced by computational protocol selection could completely mask true biological variation between samples, suggesting goal-specific best-practice guidelines for metagenomic annotation 128 . Moreover, once the samples’ functional profiles have been determined, rigorous normalization and calibration of samples are still required to allow accurate comparison across samples ( e.g.…”
Section: High-resolution Characterization Of the Microbiome's Functiomentioning
confidence: 99%